Capturing Futurity: The Artistic Exchange of Alvin Langdon Coburn and H. G. Wells - Margaret J. Schmitz (British Art Studies, 2022)
During the first decade of the twentieth century, the American-born British photographer Alvin Langdon Coburn renounced pictorialism as he documented New York City’s unprecedented architecture. Scholars have suggested that Coburn’s shift from pictorialism occurred after 1910 when his awareness of modern art movements solidified. However, this article demonstrates that Coburn’s experimentation with radical aesthetics began earlier and was instigated by his friendship with English science fiction writer H. G. Wells. Coburn formulated a visual language of futurity as he interpreted Wells’s fantastical texts in his photographs of New York. In doing so, he captured the modern metropolis’s inherent abstraction and explored how a photographed moment could be temporally estranged from the present by infusing it with a sense of the future. While Coburn’s friendship with Wells had a significant impact on his maturation as an artist, their artistic exchange has not been given adequate scholarly attention until now.